99MTC RBC Scintigraphy in the Diagnosis of Hepatic Haemangioma - Haque, Mohammad Majharul; Jannat, Syeda Nur E; Salimullah, ASM; Saha, Amitav; Datta, Ponkaj Kanti (Journal of Dhaka Medical College, 2023)
Abstract not available J Dhaka Med Coll. 2022; 31(1) : 167-169